1995
DOI: 10.1074/jbc.270.21.12730
|View full text |Cite
|
Sign up to set email alerts
|

A Chimeric Study of the Molecular Basis of Affinity and Selectivity of the κ and the δ Opioid Receptors.

Abstract: Within the large family of G-protein-coupled receptors, a picture is emerging which contrasts the binding of small ligands and the binding of peptides to the seven-helix configuration of the proteins. Because of its unique richness in both peptide and non-peptide ligands, the opioid receptor family offers several advantages for achieving a better understanding of similarities and differences in ligand/receptor interactions across different classes of agonists and antagonists. Since multiple, naturally occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
104
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 32 publications
6
104
0
Order By: Relevance
“…In a study of 5/x chimera, it was found that a chimeric mutant possessing the C-terminal portion (from helix 5 to the C-terminus) of the receptor could bind U50,488 with affinities very similar to that of the x wild type. Other ~/x chimera showed decreased binding for U50,488 relative to the wild type x receptor [15].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In a study of 5/x chimera, it was found that a chimeric mutant possessing the C-terminal portion (from helix 5 to the C-terminus) of the receptor could bind U50,488 with affinities very similar to that of the x wild type. Other ~/x chimera showed decreased binding for U50,488 relative to the wild type x receptor [15].…”
Section: Discussionmentioning
confidence: 92%
“…Recently, a more comprehensive study of the molecular basis of affinity and selectivity between ~ and x receptors has appeared which examines the binding of various selective and non-selective, peptide and non-peptide, agonist and antagonist opioid ligands to 6, K, and 5/K chimeric receptors [15]. Some of the most interesting results from this study regard the selectivity of enkephalin and dynorphin to ~ and x receptors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations